1960
DOI: 10.1107/s0365110x60000510
|View full text |Cite
|
Sign up to set email alerts
|

The accurate determination of the position and shape of heavy-atom replacement groups in proteins

Abstract: If two isomorphous heavy-atom derivatives of a protein are available with structure factors 2/1 and F2 respectively, then a Patterson synthesis with coefficients (IF1[ -IF2[) 2 will give accurate information about the relative position and shape of the heavy-atom peaks in the two compounds. IntroductionGreen, Ingrain & Perutz (1954) introduced the method of isomorphous replacement with heavy atoms to the X-ray analysis of the centro-symmetric zone of horse haemoglobin. In order to determine the phase angle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

1963
1963
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 2 publications
2
57
0
Order By: Relevance
“…For weak derivatives, an accurate knowledge of the scale factor might not be required (Rossmann, 1960); however, it has been shown that adjustment of the scale factor to compensate for the additional scattering power of heavy atoms for strong derivatives can lead to significant improvements (Nikonov, 1983). Although individual structure-factor amplitudes might grow stronger with X-ray dose, the total scattering power will normally decrease during an RIP experiment.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For weak derivatives, an accurate knowledge of the scale factor might not be required (Rossmann, 1960); however, it has been shown that adjustment of the scale factor to compensate for the additional scattering power of heavy atoms for strong derivatives can lead to significant improvements (Nikonov, 1983). Although individual structure-factor amplitudes might grow stronger with X-ray dose, the total scattering power will normally decrease during an RIP experiment.…”
Section: Figurementioning
confidence: 99%
“…1) is similar to that corresponding to an MIR experiment (Kendrew et al, 1958), where F const can be thought of as the structure factor belonging to the native structure, whereas F before and F after can be seen as equivalent to two different heavy-atom derivatives. Rossmann (1960) Harker section of a calculated data series for turkey egg-white lysozyme (TEL) in space group P2 1 , based on PDB code 1ljn. TEL has four disulfide bonds, three of which were subsequently altered.…”
Section: Theorymentioning
confidence: 99%
“…One of these related to determining the relative positions of heavy atoms. By writing a Fourier summation program in machine code for the recently homebuilt EDSAC2 computer (situated across the quadrangle in the Mathematical Laboratory), and by virtue of the 3-dimensional data Max and Ann Cullis had collected, I was able to develop a simple and unambiguous solution of the relative heavy atom sites (Rossmann, 1960) within my first 3 months in Cambridge. Max was delighted and brought in all the old hands like Bernal, Sir Lawrence, and Dorothy Hodgkin to show them the new results.…”
Section: Michael Rossmann Was Born In Frankfurt (M) Germany In 1930mentioning
confidence: 99%
“…Over the next few months, and later in collaboration with David Blow, it was possible to develop many of the techniques that are now standard fare in protein structure determinations. These included heavy atom refinement procedures (Rossmann, 1960), the use of anomalous dispersion for heavy atom site determination (Rossmann, 1961) and phase improvement, single isomorphous replacement (Blow & Rossmann, 1961), and phase combination (Rossmann & Blow, 1961). The other things that stand out in my recollections of my first year in Cambridge are punting parties along the Cam, scones at the "Orchard" in Granchester (while wasps were busy competing for the jam), unlocking large iron gates to the Old Cavendish Site with illegal copies of an enormous key possessed by everybody, and 2-way traffic in Petty Cury, a very narrow street leading to Cambridge's market place.…”
Section: Michael Rossmann Was Born In Frankfurt (M) Germany In 1930mentioning
confidence: 99%
“…Isomorphous replacement requires the preparation of a crystal in which very few heavy atoms are bound at identical points in each unit cell without introducing significant conformational changes (Blundell & Johnson, 1976). Heavy-atom sites in the unit cell may then be located with difference Patterson methods (Rossmann, 1960). When crystals contain more than a few bound heavy atoms, difference Patterson maps are not readily interpretable (Dodson & Vijayan, 1971).…”
Section: Introductionmentioning
confidence: 99%